Consumers' attitude toward Facebook advertising - Ferreira, Fátima (2017)
This paper aims to provide a closer look at consumers’ attitude toward Facebook advertising by providing a comparison between attitude toward brand posts and ads, a topic that has been disregarded in the extant literature. It also considers the relationship with the users’ ad avoidance and electronic word-of-mouth communication. An exploratory quantitative analysis was performed by means of a structured self-administered questionnaire. 385 individuals aged between 18 and 44 participated in the study. The results include evidence on respondents’ more favourable attitude toward brand posts than toward Facebook ads. Moreover, ads are considered more annoying by those who spend more time on Facebook. These results help shed the light on how Facebook users handle ads and brand posts, offering some clues for a more effective social media marketing strategy.